Recent advances in the biomimicry of structural colours. (11th August 2016) - Dumanli, Ahu Gümrah; Savin, Thierry
Abstract : This review presents the recent progress in mimicking the shiny and iridescent structural colours found in nature. Abstract : Nature has mastered the construction of nanostructures with well-defined macroscopic effects and purposes. Structural colouration is a visible consequence of the particular patterning of a reflecting surface with regular structures at submicron length scales. Structural colours usually appear bright, shiny, iridescent or with a metallic look, as a result of physical processes such as diffraction, interference, or scattering with a typically small dissipative loss. These features have recently attracted much research effort in materials science, chemistry, engineering and physics, in order to understand and produce structural colours. In these early stages of photonics, researchers facing an infinite array of possible colour-producing structures are heavily inspired by the elaborate architectures they find in nature. We review here the recent technological strategies employed to artificially mimic the structural colours found in nature, as well as some of their current and potential applications.